EGMR 27510/08 vom 17. Dezember 2013 , CASE OF PERİNÇEK v. SWITZERLAND - Hudoc Ch (2013)
Remainder inadmissible;Violation of Article 10 - Freedom of expression -General (Article 10-1 - Freedom of expression);Pecuniary damage - claim dismissed;Non-pecuniary damage - finding of violation sufficient; Violation: 10;10-1